Potential impacts of drought tolerant maize: New evidence from farm-trials in Eastern and Southern Africa - Kostandini, Genti; Tahirou, Abdoulaye; Erenstein, Olaf; Sonder, Kai; Guo, Zhe; Setimela, Peter; Menkir, Abebe (2015)
We estimate the impact of drought tolerant maize varieties in 13 countries in sub-Saharan Africa using geo referenced farm-trial data from 49 locations in eastern and southern Africa. Planting dates were matched with rainfall data in order to generate better drought risk zones in each country. Maize drought tolerant varieties perform better than popular commercial maize varieties grown in sub-Saharan Africa. Estimates are in the range of $132-$353 million to producers and consumer accruing in the 13 countries during the 2017-2016 period. Analysis of risk based on higher moments of yield distribution points out that there are drought tolerant varieties that have the same level of risk but offer higher overall gains compared to popular commercial varieties.